2015
DOI: 10.15376/biores.11.1.385-399
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis and Stability Evaluation of Ag Nanoparticles Using Bamboo Hemicellulose

Abstract: The unique physico-chemical properties of silver nanoparticles (Ag NPs) have opened up the opportunity for their use in many promising physicochemical and biomedical applications. In this study, an economically feasible approach to green synthesis of silver nanoparticles (Ag NPs) is described using hemicellulose from bamboo. Simultaneously, glucose was used as the reducing agent, and distilled water was used as the reaction medium. UV-vis spectroscopy and transmission electron microscopy were used to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(35 reference statements)
2
9
0
Order By: Relevance
“…The extraction of hemicelluloses from plant sources is extensively applied as a primary step in the preparation of other significant nanoparticles. Using hemicellulose from bamboo as an additive and glucose as a reducing agent, the nanosized silver particles were synthesized 277 , by the addition of hemicellulose at high concentrations resulted in 5 to 20 nm-sized silver particles. Likewise, hemicelluloses are useful as a tumbling agent in nanosized metal (e.g.…”
Section: Fabrication Of Hemicellulose Nanoparticlesmentioning
confidence: 99%
“…The extraction of hemicelluloses from plant sources is extensively applied as a primary step in the preparation of other significant nanoparticles. Using hemicellulose from bamboo as an additive and glucose as a reducing agent, the nanosized silver particles were synthesized 277 , by the addition of hemicellulose at high concentrations resulted in 5 to 20 nm-sized silver particles. Likewise, hemicelluloses are useful as a tumbling agent in nanosized metal (e.g.…”
Section: Fabrication Of Hemicellulose Nanoparticlesmentioning
confidence: 99%
“…Both were found to exhibit good reactivity for reducing these metals; however, the metal particles were observed to be reduced by the hemicelluloses aggregated toward larger particles. Pang et al [40] have reported that hemicellulose itself could not convert Ag + to Ag 0 and the formation rate of the nanoparticles increased with the addition of glucose. Oxygen atoms of the hydroxyl and carboxylate groups in hemicellulose contain a lone pair of electrons, enabling them to bind with Ag+ ions, which is subsequently reduced by the hemiacetal groups of glucose.…”
Section: Xps Analysismentioning
confidence: 99%
“…Investigating the QTMC concentration effect before the formation of QTMC-AgNPs, the absorbance increased with a small blue shift as the concentration of the QTMC saccharide unit increased (Figure d) due to the higher capping efficiency of silver nanoparticles. This implies that the concentration of QTMC played a significant role in the optical property of the synthesized QTMC-AgNPs …”
Section: Resultsmentioning
confidence: 98%
“…This implies that the concentration of QTMC played a significant role in the optical property of the synthesized QTMC-AgNPs. 58 Figure 3 shows the ATR-FTIR spectra of CTS, QTMC, and QTMC-AgNPs. To begin, the absence of vibrational frequency at about 1577 cm −1 in the QTMC spectrum, which was induced by N−H bond angular deformation of amino groups on the CTS backbone, is the first evidence of CTS quaternization.…”
Section: Characterizationmentioning
confidence: 99%